The performance of the school principal was reviewed from leadership style, discipline, satisfaction, and motivation in primary schools in the coordinator of the jaten education district area, karanganyar regency - Ekowati Sarjiyanti; Istatin; Sudarwati (Institute of Computer Science (IOCS), 2024)
Finding out how leadership style, work discipline, job happiness, and motivation all play a role in Jaten District school principals' success is the overarching goal of this study. A quantitative research design is utilised in this research approach. A total of 135 Jaten District public school teachers made up the study's population. A total of 135 educators participated in the survey, which was selected using a census-style sampling method. Gathering information using surveys. The statistical analysis of data makes use of the following methods: coefficient of determination, multiple linear regression test, F test, and t test. School principals' performance in Jaten District is impacted, to a lesser but statistically significant degree, by leadership style, work, job satisfaction, and motivation. Based on the findings, school principals in the Jaten sub-district should keep working on their leadership skills, work discipline, job happiness, and drive to achieve even greater results